Psychological Strategies and Protocols for Promoting School Well-Being: A Systematic Review - Limone, Pierpaolo; Toto, Giusi Antonia (Frontiers in Psychology, 2022)
Physical, socio-economic, cultural and mental challenges faced by students have been associated with adverse impacts on school wellbeing, resulting in increased school dropout and deviant behaviour. This systematic review has analysed the present knowledge on factors associated with school dropouts to identify psychological interventions for promoting school wellbeing. A systematic search was done of the ScienceDirect, APA PsycINFO, Emerald and Google Scholar electronic databases. A hand-search was also done of the reference list of the included studies. The initial search resulted in 448 studies, and the search of the references list of the considered studies resulted in 28 more articles. The application of the eligibility criteria resulted in the inclusion of 38 studies in the review. The study established several factors associated with school dropouts and social deviance, such as school climate, school structure, and those defining social interaction among students. Mental and emotional health was identified as the main factor influencing school dropout and social deviance. A positive school climate should be the primary consideration for promoting school wellbeing. School administrations, teachers, and parents should collaborate to positively improve conditions in schools.